2017
DOI: 10.3390/ijms18040845
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Blood-Based Biomarkers, α2,3-Sialic Acid PSA and PHI, for High-Risk Prostate Cancer Detection

Abstract: Prostate Specific Antigen (PSA) is the most commonly used serum marker for prostate cancer (PCa), although it is not specific and sensitive enough to allow the differential diagnosis of the more aggressive tumors. For that, new diagnostic methods are being developed, such as PCA-3, PSA isoforms that have resulted in the 4K score or the Prostate Health Index (PHI), and PSA glycoforms. In the present study, we have compared the PHI with our recently developed PSA glycoform assay, based on the determination of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 32 publications
1
47
0
1
Order By: Relevance
“…Many studies have been done which focus glycans as biomarkers in prostate cancer 3 , especially N-glycan alterations of PSA [9][10][11][12]39,43,44 . Previous studies have revealed that not all patients can be detected by measuring the increase focusing only on a specific glycan structure such as α2,3-sialyl or LacdiNAc residues [9][10][11][12]43,44 . Assessing cancer-specific changes in combination with other target may improve accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have been done which focus glycans as biomarkers in prostate cancer 3 , especially N-glycan alterations of PSA [9][10][11][12]39,43,44 . Previous studies have revealed that not all patients can be detected by measuring the increase focusing only on a specific glycan structure such as α2,3-sialyl or LacdiNAc residues [9][10][11][12]43,44 . Assessing cancer-specific changes in combination with other target may improve accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth comparing the clinical performance of PSA glycoprofiling in serum applied to PCa diagnostics with the performance of PSA and PHI tests. The PSA tests afford AUC ¼ 0.68 [14] and the PHI test could discriminate between PCa and BPH patients with AUC ¼ 0.74 [54]. The detection of increased levels of a-2,6-SA by the SNA lectin does not offer any advantage in terms of clinical performance (AUC ¼ 0.63) [55] over the PSA and PHI tests.…”
Section: Resultsmentioning
confidence: 99%
“…Eluted and bound fractions were collected and fPSA was detected in both fractions to calculate the a-2,3-SA percentage of PSA and a-2,6-SA percentage of PSA. The results indicate that the a-2,3-SA percentage cannot be applied to PCa diagnostics because no significant differences were observed between BPH (PSA level in the range 3.9 -14.5 ng ml 21 [54]. Out of five different Sepharose-bound lectins investigated for glycoprofiling of fPSA, MAA, in particular, was capable of distinguishing between PCa patients and BPH patients with a high statistical significance ( p , 0.001) [63].…”
Section: Prognostic Prostate Cancer Biomarkers 4121 Sialylation Cmentioning
confidence: 92%
See 1 more Smart Citation
“…Five studies present their basic research data using PCa cell lines [ 14 , 15 , 16 , 17 ] or summarize data on cancer/testis antigens (CTAs) as potential PCa biomarkers [ 18 ]. Serum markers are the subject in the vast majority of publications ( n = 8) with focus on PCa diagnostic and prognostic [ 19 , 20 , 21 , 22 , 23 ] or evaluation of advanced/metastatic disease stages [ 24 , 25 , 26 ]. Two of the four reviews further summarize biomarkers for PCa diagnostic [ 27 ] or active surveillance [ 28 ] while the other two reviews have special topics like nanoparticles as theranostic vehicles [ 29 ] or PCa stem cells [ 30 ].…”
Section: Overviewmentioning
confidence: 99%